Reviewing Pillar 2 regulations: credit concentration risk. Issue 3 (8th July 2019) - Prorokowski, Lukasz; Prorokowski, Hubert; Bongfen Nteh, Georgette
Abstract : Purpose: This paper aims to analyse the recent changes to the Pillar 2 regulatory-prescribed methodologies to classify and calculate credit concentration risk. Focussing on the Prudential Regulation Authority's (PRA) methodologies, the paper tests the susceptibility to bias of the Herfindahl–Hirscham Index (HHI). The empirical tests serve to assess the assumption that the regulatory classification of exposures within the geographical concentration is subject to potential misuse that would undermine the PRA's objective of obtaining risk sensitivity and improved banking competition. Design/methodology/approach: Using the credit exposure data from three global banks, the HHI methodology is applied to the portfolio of geographically classified exposures, replicating the regulatory exercise of reporting credit concentration risk under Pillar 2. In doing so, the validity of the aforementioned assumption is tested by simulating the PRA's Pillar 2 regulatory submission exercise with different scenarios, under which the credit exposures are assigned to different geographical regions. Findings: The paper empirically shows that changing the geographical mapping of the Eastern European EU member states can result in a substantial reduction of the Pillar 2 credit concentration risk capital add-on. These empirical findings hold only for the banks with large exposures to Eastern Europe and Central Asia. The paper reports no material impact for the well-diversified credit portfolios of global banks. Originality/value: This paper reviews the PRA-prescribed methodologies and the Pillar 2 regulatory guidance for calculating the capital add-on for the single name, sector and geographical credit concentration risk. In doing so, this paper becomes the first to test the assumptions that the regulatory guidance around the geographical breakdown of credit exposures is subject to potential abuse because of the ambiguity of the regulations.